Analysis and substantiation of methods for determining water consumption of haip-pasture herbs in conditions of irrigation by raining - N. N. Dubenok; D. V. Yalansky; Yu. A. Mazhaysky; O. V. Chernikova; Yu. N. Dubrova (Овощи России, 2021)
Relevance. The most important element of the operational regime of irrigation is the correct (timely) appointment and timing of irrigation, taking into account the biological characteristics of crops, weather conditions and the mechanical composition of the soil.Methods. In this work, the results of the calculation of the irrigation regime of the hay-pasture grass mixture for the growing season april-october 2016-2018 were presented, on the basis of which the values of the water consumption of the crop, the average values of bioclimatic and biothermal coefficients in relation to sod-podzolic loamy soils in the northeastern zones of the Republic of Belarus. The calculations were carried out by the water balance method, as well as by the method of maximum daily air temperatures.Results. As a result of calculating bioclimatic and biothermal coefficients and values of water consumption for the growing seasons. It was found that their highest values in all years of research were recorded in the variant with a pre-irrigation humidity level of 80% of the lowest moisture capacity, while their lowest values were observed in the variant with natural humidification. At the same time, as a result of calculations, it was established that the highest values of bioclimatic coefficients corresponding to the variant 80% of HB took the following values: 0.88; 0.72 and 0.66, the smallest are 0.71; 0.64 and 0.50, and the largest values of the biothermal coefficients were: 0.13; 0.15 and 0.15, the smallest are 0.09; 0.13 and 0.10, respectively, for the growing seasons. The largest values of water consumption, calculated by the water balance method, corresponding to the option 80% of the HB took the following values: 423.0; 462.0 and 440.0 mm, the smallest in this case were: 334.0; 404.0; and 331.0 mm, and the highest values of water consumption, calculated by the method of maximum daily temperatures were: 439.4; 420.0 and 432.2, while the smallest were equal: 318.7, 396.4 and 325.7 mm, respectively, for the growing seasons.